SAT0357 Features associated with moderate to high risk of malnutrition in a cohort of patients with systemic sclerosis. (15th June 2017) - Marcaida, PM; Vanesa, D; Martire, V; Melo, F; Secco, A; Mamani, M; Scarafia, S; Lazaro, M; Cusa, A; Cusa, F; Caputo, V; Sarano, J; et al.
Abstract : Background: It is estimated that about 28% of Systemic Sclerosis (SS) patients have moderate to high risk of malnutrition. Objectives: to evaluate differences between SS patients with moderate to high risk of malnutrition and those with low risk. Methods: cross-sectional, observational, multicentric study. We included patients with SS according to ACR-EULAR 2013 classification criteria. Patients were classified in groups depending on whether they were in low or moderate-high risk of malnutrition, according to the screening method for detection of adult malnutrition (MUST). Were evaluated: disease duration, disease subtype (limited or diffuse), presence of microstomia, xerostomia, active or past digital ulcers, amputations, arthritis, Rodnan Score, gastroesophageal and bowel involvement, anxiety and depression, and hands functionality by Duruöz Index. Continuous variables were described as median (IQR) or mean (SD) and percentages for categorical variables. Mann Whitney or t-test was used for continuous variables, and Fisher exact test or chi squared for categorical variables. A p <0.05 was considered significant. A multivariate analysis was made taking MUST as a dependent variable. Results: 116 patients were included. Thirty percent were at moderate to high risk of malnutrition. These patients experienced significantly higher frequency of diffuse SS (49% vs 21%, p =0, 003), bowel involvement (49% vs 27%. p =0, 02), gastroesophageal involvement (74% vs 48%, p =0, 009), higher cutaneous involvement ( median 12 vs 6, p =<0, 01), microstomia (40% vs 15%, p =0, 003), worst hand functionality ( median: 11 vs 3, p =0, 02), and moderate-severe depression (37% vs 16%, p =0, 012). Also, men experienced a higher moderate-high risk of malnutrition (20% vs 6%, p =0, 02). In the multivariate analysis, the male sex (OR 4.55, 95% CI 1.11–20, p=0.03), the Rodnan score >9 (OR 3.13, 95% CI, 95% CI, p=0, 01), and gastroesophageal involvement (OR 2.87, 95% CI 1.07–7.73, p=0.03), were independently and statistically significant. Conclusions: These results highlight the importance of assessing the nutritional status of our SS patients. Disclosure of Interest: None declared